In-kind donations to healthcare facilities during COVID-19: Experiences from a large medical center in northern Taiwan. Issue 7 (1st July 2021) - Lin, Ching-Wei; Hsu, Ya-Chuan; Wu, Chien-Cheng; Chen, Tzeng-Ji; Hwang, Shinn-Jang
Abstract : Background: In early 2020, a global outbreak of 2019 novel coronavirus disease (COVID-19) caused high mortality rates and public panic. Worldwide demand for personal protective equipment has risen, with diminishing supplies and shortages reported. During the pandemic, charitable donations have been made by the public, aimed at helping medical staff. Based on the open data, we investigate the charitable in-kind donations received by a large medical center in northern Taiwan (Taipei Veterans General Hospital [TPEVGH]) in Taiwan during the pandemic. Methods: The period of investigation was the first half of the year 2020. TPEVGH has received various public donations. The list of donations published on the hospital's official website was analyzed. The variables in the analysis were donation category, donation percentage, number of donations, and total donation amount. Results: Most in-kind donations were food and beverages (55.1%), with a monetary value of 3 124 510 New Taiwan Dollars (NTD) (24.3%). Medical equipment accounted for the second-highest number of items (34.8%) but was the highest monetary value (70.6%; 9 275 945 of 12 875 855 NTD). Daily necessities accounted for the lowest number of items (10.1%) and had a total monetary value of 475 400 NTD (3.7%). Over two-thirds were beverages (68.4%), all of which were bottles or cans for easy storage. Despite only five items (13.2%) being juice, the donation size was the largest, accounting for nearly half (47.1%) of the total monetary value. Only one item was fruit, which was high-class organic apples. The monetary value of this item was the highest (7.8%) among all donated food. Most donated snacks were biscuits. Conclusion: During the COVID-19 pandemic, most public donations to TPEVGH were food and daily necessities. While every donation should be appreciated, accepting high volumes of donations might incur donation management problems. Further research could be focused on managerial aspects, for example, quality and safety checking, storage, and distribution.